Return-to-work intervention for cancer survivors: budget impact and allocation of costs and returns in the Netherlands and six major EU-countries. Issue 1 (December 2015) - Mewes, Janne; Steuten, Lotte; Groeneveld, Iris; de Boer, Angela; Frings-Dresen, Monique; IJzerman, Maarten; van Harten, Wim
Abstract Background Return-to-work (RTW)-interventions support cancer survivors in resuming work, but come at additional healthcare costs. The objective of this study was to assess the budget impact of a RTW-intervention, consisting of counselling sessions with an occupational physician and an exercise-programme. The secondary objective was to explore how the costs of RTW-interventions and its financial revenues are allocated among the involved stakeholders in several EU-countries. Methods The budget impact (BI) of a RTW-intervention versus usual care was analysed yearly for 2015–2020 from a Dutch societal- and from the perspective of a large cancer centre. The allocation of the expected costs and financial benefits for each of the stakeholders involved was compared between the Netherlands, Belgium, England, France, Germany, Italy, and Sweden. Results The average intervention costs in this case were €1, 519/patient. The BI for the Netherlands was €-14.7 m in 2015, rising to €-71.1 m in 2020, thus the intervention is cost-saving as the productivity benefits outweigh the intervention costs. For cancer centres the BI amounts to €293 k in 2015, increasing to €1.1 m in 2020. Across European countries, we observed differences regarding the extent to which stakeholders either invest or receive a share of the benefits from offering a RTW-intervention. Conclusion The RTW-intervention is cost-saving from a societal perspective. Yet, the total intervention costs are considerable and, in many European countries, mainly covered by care providers that are not sufficiently reimbursed.